"The same but different" Triaging in primary healthcare settings: A focused ethnography study. Issue 1 (February 2021) - Reblora, Julienne Mae; Dong, Lijuan; Lopez, Violeta; Goh, Yong-Shian
ABSTRACT: Aims: To explore the experiences of nurses working in triage stations of primary health care centres. Background: Primary healthcare system evolves according to the demographical and epidemiological transitions within the nation. The escalating demand on healthcare due to the aging population have seen a rising need from patients with onset of an acute condition or the deterioration of chronic conditions. This has led to a stress in the primary healthcare system where more patients were referred to the tertiary hospitals for the management of more complex conditions. Design: A focused ethnographic study was conducted in five primary healthcare centres in Singapore. Twenty-two registered nurses were selected through purposive sampling where data was collected through field notes, covert observations and semi-structured interviews from August 2017 to November 2017. Source, time, space and person triangulation generated emerging themes. Results: Thematic analysis revealed a central exhaustive description of 'the same but different', was supported by three themes including: valuing previous nursing experience; (2) acknowledging patients' and relatives' concerns, and (3) affirming of nurses' triage decisions with primary health care doctors. Conclusions: This study provides a pioneering exploration of the experiences of nurses working in a triage area within primary healthcare centres. Data generated herein afford a deeper understanding of the decision and communication involving primary healthcare triage nurses and the importance of interprofessional communication between doctors and nurses in order for them to gain understanding on their decision making process.